Simple competitive two-step RT-PCR assay to monitor minimal residual disease in CML patients after bone marrow transplantation - Moravcová, J; Lukásová, M; Starý, J; Haskovec, C (Leukemia, 1998)
Quantitative reverse transcription-polymerase chain reaction (Q-RT-PCR) assessing the amount of transcripts of the BCR/ABL gene, the molecular marker of chronic myeloid leukemia (CML), is the only method sensitive enough for monitoring of minimal residual disease (MRD) in CML patients after bone marrow transplantation (BMT). In this study we present a simple modification of competitive Q-RT-PCR using natural competitors from cell lines K562 and BV173. The competitors were used in the form of unpurified RNA in cell lysates which ensured their high stability. Mixing competitors and samples before RNA extraction eliminated problems with quantification of cDNA or RNA entering the competitive reaction and with checking for the RNA quality and reverse transcription (RT) efficiency. The bulk of the malignant clone was expressed as the number of leukemic cells in 10(6) leukocytes when the overproduction of the BCR/ABL mRNA in the cell lines we used as competitors was taken into account. It was found to be 82-fold and 14-fold in K562 and BV173, respectively, in comparison with 100% Ph-positive CML standard. The assay reliability was verified by comparison of results with the mathematical model of competitive PCR. The assay is highly reproducible and sensitive (10(-5)). Its accuracy was proved to be excellent in a wide range of malignant cell concentrations. The method is demonstrated on three CML patients suffering from MRD after BMT. In conclusion, this method fulfills all criteria of competitive Q-RT-PCR. Because of its simplicity it is suitable for clinical laboratories and due to the high stability of the lysates used it may serve in the standardization of results between different laboratories.
Keywords: geny abl; Binding, Competitive; Genes, abl; chemické modely; Models, Chemical; chronická myeloidní leukemie; Humans; kompetitivní vazba; polymerázová řetězová reakce; Polymerase Chain Reaction; Reproducibility of Results; transplantace kostní dřeně; reziduální nádor; lidé; Bone Marrow Transplantation; reprodukovatelnost výsledků; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Neoplasm, Residual